Flexible bronchoscopy - Wang, Ko-Pen.; Mehta, Atul C.; Turner, J. Francis; Wiley InterScience (Online service) (Hoboken : John Wiley & Sons, 2012)
With the development of new instruments and the refining of new techniques, flexible bronchoscopy has become one of the most frequently performed invasive procedures in pulmonary medicine. This new edition of Flexible Bronchoscopy is an essential addition to the bronchoscopist's bookshelf. It highlights possible complications, contra-indications and precautions. In addition it addresses all current techniques and future technologies in interventional bronchoscopy. For ease of use Flexible Bronchoscopy is divided into four major sections:Fundamentals of BronchoscopyDiagnostic BronchoscopyTherapeu.
Front Matter -- Fundamentals of Bronchoscopy. Bronchoscopy in the New Millennium / Noriaki Kurimoto, Teruomi Miyazawa -- Infection Control and Radiation Safety in the Bronchoscopy Suite / Prasoon Jain, Atul C Mehta -- Examination of the Larynx through the Flexible Bronchoscope / Navatha Kurugundla, Adnan Majid, Luis F Riquelme, Arthur W Sung -- Applied Anatomy of the Airways / Mani S Kavuru, Atul C Mehta, J Francis Turner -- Anesthesia for Flexible Fiberoptic Bronchoscopy / Mario Gomez, Gerard A Silvestri -- Flexible Bronchoscopy Training / Momen M Wahidi, Navreet Sandhu Sindhwani, Scott L Shofer, Ali I Musani -- Indications and Contraindications in Flexible Bronchoscopy / Robert F Browning, J Francis Turner, Ko-Pen Wang -- Diagnostic Bronchoscopy. Bronchoscopy for Airway Lesions / Heinrich D Becker -- Bronchoscopic Lung Biopsy / Rajesh R Patel, James P Utz -- Bronchoalveolar Lavage / Brian Palen, Richard Helmers -- Transbronchial Needle Aspiration for Cytology and Histology Specimens / Ko-Pen Wang, Atul C Mehta, J Francis Turner -- The Utilization of Autofluorescence in Flexible Bronchoscopy / Taichiro Ishizumi, Stephen C T Lam -- Endobronchial Ultrasound / Heinrich D Becker -- Application and Limitations of Virtual Bronchoscopic Navigation / Fumihiro Asano -- Therapeutic Bronchoscopy. Application of Laser, Electrocautery, Argon Plasma Coagulation, and Cryotherapy in Flexible Bronchoscopy / Praveen N Mathur -- Flexible Bronchoscopy and the Application of Endobronchial Brachytherapy, Fiducial Placement, and Radiofrequency Ablation / Michael A Jantz -- Foreign Body Aspiration and Flexible Bronchoscopy / Erik Folch, Atul C Mehta -- The Role of Bronchoscopy in Hemoptysis / Sunit R Patel, James K Stoller -- Flexible Bronchoscopy and the Use of Stents / Ko-Pen Wang, Atul C Mehta, J Francis Turner -- Photodynamic Therapy in Lung Cancer / Harubumi Kato, Jitsuo Usuda, Yasufumi Kato -- Balloon Bronchoplasty / Sara R Greenhill, Kevin L Kovitz -- Special Considerations. Rigid Bronchoscopy / J Francis Turner, Ko-Pen Wang -- Pediatric Flexible Bronchoscopy for Adult Bronchoscopists / Xicheng Liu, Shunying Zhao, Peter Mogayzel -- Bronchoscopy in the Intensive Care Unit / Alex Chen, Marian H Kollef -- Bronchial Thermoplasty / Samir Makani, Michael J Simoff -- Index.
Print version record.
Keywords: Bronchoscopy; Bronchial Diseases -- diagnosis; Bronchial Diseases -- therapy; Bronchoscopy -- methods; Medicine; Bronchoscopy; Electronic books